Long-Term Zidovudine Therapy and Whether It is a Trigger of Vitamin B12 Deficiency: A Case Study of Megaloblastic Anemia at the University of Zambia Teaching Hospital - Kaweme, Natasha Mupeta; Butress, Sahar Mounir Nagib; Mantina, Hamakwa Muluti (Case Reports in Hematology, 2022)
Macrocytic anemia is frequently observed in adult HIV-infected patients treated with nucleoside reverse transcriptase inhibitors and with vitamin B12 and folate deficiency. In this case report, we discuss a 52-year-old nonvegetarian male on long-term antiretroviral therapy for 5 years, presenting with severe macrocytic anemia (hemoglobin, 3.7 g/dL; mean corpuscular volume, 119.6 fL) and leukopenia (2.71∗109/L), who was diagnosed with megaloblastic anemia caused by vitamin B12 deficiency following laboratory investigations. Parenteral vitamin B12 replacement therapy was initiated, with an early response observed. Notwithstanding, the treatment response was not sustained as the patient later presented with refractory anemia and persistence of macrocytosis. Discontinuation of zidovudine with concurrent vitamin B12 administration promptly improved the patient’s clinical deficiency symptoms. At the end of 3 months, the patient had a complete hematological recovery. The deficiency of vitamin B12 disrupts DNA synthesis inhibiting effective hematopoiesis in all cell lines, particularly erythroid precursors and further promotes reversible bone marrow failure. Long-term ART therapy with zidovudine causes cytotoxicity in myeloid and erythroid precursors and induces bone marrow suppression. Whether long-term zidovudine consumption induced lower levels of vitamin B12 and subsequent megaloblastic anemia requires in-depth research and exploration.